2014
DOI: 10.1167/iovs.13-12948
|View full text |Cite
|
Sign up to set email alerts
|

The Role of K+and ClChannels in the Regulation of Retinal Arteriolar Tone and Blood Flow

Abstract: These results suggest that Cl(-) channels in retinal arteriolar smooth muscle limit resting blood flow and play an obligatory role in Et1 responses. K(+)-channel activity promotes basal flow but exerts little modifying effect on the Et1 response. Cl(-) channels may be appropriate molecular targets in retinal pathologies characterized by increased Et1 activity and reduced blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
(87 reference statements)
0
10
0
Order By: Relevance
“…In rabbits, 50 nmol/L iberiotoxin had no effect on resting pial arteriolar diameter, whereas 100 nmol/L produced only a 3% constriction (1371). In fawn hooded rats, administration of penetrem A or iberiotoxin into eyes results in no significant change in retinal arteriolar diameter, although both produced a 10% decrease in arteriolar blood flow, which was computed from the vessel diameter and red blood cell velocity suggesting upstream effects (1066). Other investigators have previously reported no effect of iberiotoxin on resting retinal arteriolar diameter in Wistar rats (1030).…”
Section: Bkca Channelsmentioning
confidence: 99%
“…In rabbits, 50 nmol/L iberiotoxin had no effect on resting pial arteriolar diameter, whereas 100 nmol/L produced only a 3% constriction (1371). In fawn hooded rats, administration of penetrem A or iberiotoxin into eyes results in no significant change in retinal arteriolar diameter, although both produced a 10% decrease in arteriolar blood flow, which was computed from the vessel diameter and red blood cell velocity suggesting upstream effects (1066). Other investigators have previously reported no effect of iberiotoxin on resting retinal arteriolar diameter in Wistar rats (1030).…”
Section: Bkca Channelsmentioning
confidence: 99%
“…In isolated rat retinal arterioles, addition of ATP triggers a robust constriction of the vessels 36 , while in the presence of an intact neuropile, the vessels dilate 37 . Therefore, wherever possible, we usually try to validate key findings from our isolated arteriole preparations using ex vivo retinal whole-mounts and in vivo measurements of vessel diameter and blood flow 16 37 . Of note, new methods have recently emerged for studying small arterioles and capillaries in whole perfused porcine retinas ex vivo 38 39 .…”
Section: Discussionmentioning
confidence: 99%
“…These vessels form the main site of vascular resistance within the retinal circulation and therefore play an important role in the local control of retinal blood flow. Retinal arterioles regulate capillary blood flow in the retina by dilating or constricting their luminal diameter, mediated by changes in vascular smooth muscle contractility 10 15 16 . Understanding the molecular mechanisms through which retinal arterioles regulate retinal perfusion therefore requires preparations where the arteriolar smooth muscle cells can be accessed and studied in conditions as close to physiological as possible.…”
Section: Introductionmentioning
confidence: 99%
“…The standard inhibitor for BK channels is iberiotoxin whose high price and membrane impermeability makes its use less than ideal for studies in organ models or whole animals. The higher membrane permeability, potency and efficacy of penitrem A may recommend this IDT as a good alternative to iberiotoxin for studying BK channels in vitro and in vivo (Stewart et al 2012; Asano et al 2012; Kyle et al 2013; Needham et al 2014). …”
Section: Future Perspectivesmentioning
confidence: 99%